دراسة اقتصادية لإنتاج غراس الصنوبر البروتي (Pinus brutia) في محافظة اللاذقية - درويش, نضال; الشاطر, زهير; سليمان, عروة (Latakia University Journal -Biological Sciences Series, 2019)
The study was conducted in lattakia Governorate,Syria.the objective of the study was to study the costs of production of binus brutia used in the re-foresting of some the forest affected sites in lattakia Governorate. Analyze these costs, and calculate their economic returns optimally. The analytical descriptive approach was used to calculate, evaluate,and interpret data to reach useful scientific results. The study showed that the gross output is 1710000 sp/dunum, while the total production costs amounted to 11521809sp/dunum, and the profit feom the dunums was 5578191sp/dunum. This results in appropriate planning of the process of artificial re-foresting better and more accurately. أجريت الدراسة في محافظة اللاذقية (مشتل الهنادي)، سورية، هَدف البحث إلى دراسة تكاليف إنتاج غراس الصنوبر البروتي (Pinus brutia) المستخدمة في عملية التشجير لبعض مواقع الغابات المتضررة بفعل الحرائق في محافظة اللاذقية. والعمل على تحليل تلك التكاليف، وحساب عوائدها الاقتصادية بالشكل الأمثل. تم الاعتماد على المنهج الوصفي التحليلي في حساب المعطيات، وتقويمها، وتفسيرها للوصول إلى نتائج علمية مفيدة. بينت الدراسة أن الناتج الإجمالي يساوي 1710000 ل.س/ دونم، بينما بلغت التكاليف الإنتاجية الإجمالية 1152180.9 ل.س/ دونم، والربح من الدونم الواحد بلغ 5578191 ل.س/ دونم. وتفيد هذه النتائج في التخطيط المناسب لعملية التشجير الاصطناعي بشكل أفضل وأكثر دقة.